The madness of our lives : experiences of mental breakdown and recovery - Gray, Penny (Jessica Kingsley Publishers, 2006)
What precipitates mental breakdown? How do people experience such extremes - and how do they see others' interpretations and interventions? Most important, how do people recover from these episodes and get their lives back? These are some of the questions addressed in this anthology of first-hand accounts of mental breakdown and recovery. Eleven very different stories together shed light on what triggers mental breakdown, what it is like to be 'mad', whether treatment helps and how people reclaim themselves and their lives. Based on tape-recorded interviews with people.